Polarographic Determination and Antimicrobial Activity of Cu(II) Complex with 4-Chlorobenzylidene-4-aminoacetanilide - Riyaz Ahmad Dar; Krishna Kumar Raj (E-Journal of Chemistry)
The electrochemical behaviour of the complex of Cu(II) with 4-chlorobenzylidene-4-aminoacetanilide (CAA) was studied. It was observed that CAA forms 1:1 complex with Cu(II) in between pH 6.5 to 7.1. It was found that the reduction process of Cu(II)- CAA complex is two electron reversible reduction process at D.M.E. The logarithm value of stability constant of Cu(II)-4-Chlorobenzylidene-4-aminoacetanilide (CAA) complex has been found to be 4.85.The redox properties of the complex was extensively investigated by electrochemical method using cyclic voltammetry (CV).The Cu(II) complexes exhibited quasi-reversible single electron transfer process.The Schiff base and its complex has been screened for their in-vitro antibacterial (Escherichiacoli, Staphylococcus aureus, Vibrio cholerae and Bacillus subtilis) and antifungal (Aspergillus niger and Penicillium liliacinum) activities by minimum inhibitory concentration (MIC) method.